2011
DOI: 10.1371/journal.ppat.1002067
|View full text |Cite
|
Sign up to set email alerts
|

The Influenza Virus Protein PB1-F2 Inhibits the Induction of Type I Interferon at the Level of the MAVS Adaptor Protein

Abstract: PB1-F2 is a 90 amino acid protein that is expressed from the +1 open reading frame in the PB1 gene of some influenza A viruses and has been shown to contribute to viral pathogenicity. Notably, a serine at position 66 (66S) in PB1-F2 is known to increase virulence compared to an isogenic virus with an asparagine (66N) at this position. Recently, we found that an influenza virus expressing PB1-F2 N66S suppresses interferon (IFN)-stimulated genes in mice. To characterize this phenomenon, we employed several in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
256
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(262 citation statements)
references
References 50 publications
6
256
0
Order By: Relevance
“…46,74,75 Inhibiting apoptosis of cells that produce viral progeny and promoting apoptosis of cells of the innate immune system that attack infected cells would be beneficial for the virus. 152 In conclusion, influenza viruses evaluated under a variety of experimental protocols do appear to express a range of virulence or pathogenic capabilities. Identification of specific virulence determinants has proven to be difficult because of polygenic contributions to pathogenicity.…”
Section: Ns1mentioning
confidence: 98%
“…46,74,75 Inhibiting apoptosis of cells that produce viral progeny and promoting apoptosis of cells of the innate immune system that attack infected cells would be beneficial for the virus. 152 In conclusion, influenza viruses evaluated under a variety of experimental protocols do appear to express a range of virulence or pathogenic capabilities. Identification of specific virulence determinants has proven to be difficult because of polygenic contributions to pathogenicity.…”
Section: Ns1mentioning
confidence: 98%
“…The 1918 and USSR PB1-F2 proteins shared 86% amino acid identity. However, the shorter USSR PB1-F2 lacks the C-terminal domain, which contains a mitochondrial targeting sequence, mediates PB1 binding, promotes inflammation, and interferes with type I IFN signaling (2,17,20,30). In addition to a full-length C-terminal domain, the 1918 PB1-F2 protein has a serine at position 66 (Fig.…”
Section: Characterization Of Recombinant Viruses With Altered Pb1-f2mentioning
confidence: 99%
“…PB1-F2 also interacts with PB1 and regulates viral polymerase activity in a cell-type-and strain-specific manner (13,17,20), and a role of PB1-F2 in the interaction with the cellular antiviral response has been reported. However, while one study observed a PB1-F2-mediated exacerbation of beta interferon (IFN-␤) expression in human lung epithelial cells, a different study demonstrated an inhibition of type I IFN signaling that was associated with interaction of PB1-F2 with the mitochondrial antiviral signaling protein (MAVS) (15,30). Finally, intranasal administration of synthetic full-length or carboxy-terminal portions of A/Brevig Mission/ 1/1918 (1918) and A/Puerto Rico/8/34 (PR8) PB1-F2 peptides led to recruitment of white blood cells into the lungs and exacerbated secondary bacterial infection in mice (18,20).…”
mentioning
confidence: 99%
“…PB1-F2 has been shown to modulate the induction of type I IFN (21)(22)(23); however, its main function is to induce apoptosis in host immune cells by targeting mitochondria via the basic amphipathic helix in its Significance Apoptosis refers to the ability of a cell to undergo programmed cell death under normal physiological conditions or in response to stress signals. During infection, influenza A viruses have the capacity to induce early apoptosis of immune cells, thereby preventing them from performing their antiviral function.…”
mentioning
confidence: 99%